AI-Supported Management through Leveraging Artificial Intelligence for Effective Decision Making - Loso Judijanto; Asfahani Asfahani; Asri Ady Bakri; Edy Susanto; Ummu Kulsum (Journal of Artificial Intelligence and Development, 2025)
This study explores integrating artificial intelligence (AI) technology in management practices to improve decision-making effectiveness. This research investigates how AI-powered management systems leverage machine learning, predictive analysis, and scenario modeling to provide real-time data insights and optimize resource allocation. This research uses the Systematic Literature Review (SLR) methodology to analyze existing studies and theoretical frameworks related to AI in management. The research results reveal that AI technology contributes significantly to strategic agility, operational efficiency, and risk assessment, ultimately resulting in better decision outcomes. The study concludes that organizations must invest in talent development, ethical considerations, and cybersecurity measures to fully exploit AI's potential for effective decision-making in today's dynamic business landscape.